The SAURON project - I. The panoramic integral-field spectrograph - Bacon, R; Copin, Y; Monnet, G; Miller, B; Allington-Smith, JR; Bureau, M; Carollo, C; Davies, R; Emsellem, E; Kuntschner, H; Peletier, R; Verolme, E; et al. (2001)
A new integral-field spectrograph, SAURON, is described. It is based on the TIGER principle, and uses a lenslet array. SAURON has a large field of view and high throughput, and allows simultaneous sky subtraction. Its design is optimized for studies of the stellar kinematics, gas kinematics, and line-strength distributions of nearby early-type galaxies. The instrument design and specifications are described, as well as the extensive analysis software which was developed to obtain fully calibrated spectra, and the associated kinematic and line-strength measurements. A companion paper will report on the first results obtained with SAURON on the William Herschel Telescope.